2012
DOI: 10.1080/01635581.2012.658950
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Quercetin With Reduced Risk of Proximal Colon Cancer

Abstract: Quercetin is a flavonol that appears to be protective against several cancers, but its possible role in prevention of colorectal cancer is not yet well studied. We evaluated dietary intakes of quercetin and risk of colorectal cancer in a large case-control study conducted in Metropolitan Detroit, MI (n = 2664). The protective effects of quercetin intake, as assessed by food frequency questionnaire, were confined to risk of proximal colon cancer. Stratified analyses showed that the protective effects of quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 71 publications
3
43
0
Order By: Relevance
“…18,19) In addition to these beneficial effects, quercetin plays preventive and therapeutic roles in various types of cancer and cancer cells. [20][21][22][23][24][25] However, the anticancer effect of quercetin in NSCLC cells has been rarely addressed, and the underlying molecular mechanism remains to be determined.…”
Section: Cip1mentioning
confidence: 99%
See 1 more Smart Citation
“…18,19) In addition to these beneficial effects, quercetin plays preventive and therapeutic roles in various types of cancer and cancer cells. [20][21][22][23][24][25] However, the anticancer effect of quercetin in NSCLC cells has been rarely addressed, and the underlying molecular mechanism remains to be determined.…”
Section: Cip1mentioning
confidence: 99%
“…18,19) In addition to these beneficial effects, quercetin plays preventive and therapeutic roles in various types of cancer and cancer cells. [20][21][22][23][24][25] However, the anticancer effect of quercetin in NSCLC cells has been rarely addressed, and the underlying molecular mechanism remains to be determined.Here, we investigated the growth inhibitory role of quercetin in three NSCLC cell lines and found that its effect is p53-independent and triggered by apoptosis. Subsequent microarray analysis using H460 cells indicated that quercetin enhances the expression of genes associated with death receptor signaling and cell cycle inhibition, but decreases the expression of genes involved in nuclear factor (NF)-κB activation.…”
mentioning
confidence: 99%
“…Natural antioxidants are however gaining desired attention for their ability to protect the human body from these free radicals mediated oxidative stress reactions [9,14]. Antioxidants mediate these reactions by free radical scavenging, peroxide decomposition, suppression of singlet oxygen, enzymatic inhibition and increasing the levels of endogenous defences [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These modified foods are classified as functional foods because they contain, besides the basic nutrition, co mponents that provide health benefits [1]. The continued ingestion of food supplemented with antio xidant substances cause inhibitory effects on the proliferation o f carcinogenic cells in human beings [2][3][4]. These effects appear because the antioxidant substances are able to perform so me functions, as free radical scavenging, peroxide deco mposition, suppression of singlet oxygen, enzy matic inhibit ion [1] and increasing the levels of endogenous defences [5].…”
Section: Introductionmentioning
confidence: 99%